Electric machines : theory, operation, applications, adjustment, and control - Hubert, Charles I. (Upper Saddle River, New Jersey : Prentice-Hall, 2002)
Retaining the user-friendly style of the First Edition, the Second Edition of this unique book provides detailed information on the application and safe operation of motors, generators, and transformers at the Technology Level, and includes examples in the use of NEMA and NEC Standards. With an emphasis on current industrial standards, this book presents AC machines and transformers before DC machines, motors before generators, gives more attention to machine characteristics, and makes extensive use of NEMA standards and tables. For Applications Engineers, Electrical Engineers, Maintenance Engineers, Marine Engineers, Mechanical Engineers, Nuclear Engineers, Operating Engineers, and Petroleum Engineers, who want an easy-to-understand, yet detailed explanation of the current industrial standards in the field of Electronics.
Magnetics, Electromagnetic Forces, Generated Voltage, and Energy Conversion -- Transformer Principles -- Transformer Connections, Operation, and Specialty Transformers -- Principles of Three-Phase Induction Motors -- Classification, Performance, Applications, And Operation Of Three-Phase Induction Machines -- Single-Phase Induction Motors -- Specialty Machines -- Synchronous Motors -- Synchronous Generators (Alternators) -- Principles Of Direct-Current Machines -- Direct-Current Motor Characteristics and Applications -- Direct-Current Generator Characteristics and Operation -- Control of Electric Motors.
Includes index.
Keywords: ELECTRIC MACHINERY